Ectopic pregnancy: clinical features, management and complications - Palve, Tushar Tatyaba; Bhattacharya, Rangan; Magtangi, Vijaydeepthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: An ectopic pregnancy (EP) occurs when a fertilized ovum implants outside the normal uterine cavity 1. Ectopic pregnancy (EP) is a condition presenting as a major health problem for women of childbearing age.2 The incidence of EP varies with the population, but it has been accounted for 1-2% of all reported pregnancies. EP is one of the few medical conditions that can be managed expectantly, medically or surgically. Surgical methods are still the mainstay in the management of EP, and in developed societies, laparoscopic surgery is currently the gold standard. Methods: This is a retrospective observational study conducted in a tertiary care centre in Mumbai from November 2016 to November 2017. All patients diagnosed with ectopic pregnancy (by clinical examination, USG and/or B hCG) were included in the study. The aims and objectives of the study were to determine the demographic distribution, risk factors, clinical features, treatment modalities and complications in patients presenting with EP. Results: The incidence of ectopic pregnancies in one year was 1.17%. The commonest age of presentation of EP was between 35-40 years, most of the patients were Gravida 4 (28.57%). Majority of patients presented at a gestational age between 6-8 weeks. Most patients (64.28%) were found to have ruptured ectopic. 28.57% patients had a previous history of abortion. 14.28% of each EP were cornual and heterotopic as found intra-operatively. There was 1 interstitial and 1 scar ectopic pregnancy. The most common associated risk factor in these patients were a history of some form of pelvic surgeries in the past. Most of these patients presented with pain abdomen and were found to be anaemic and with a shock index (SBP/HR) of > 0.8. 64.28% of cases were diagnosed by combination of TVS and serum BhCG levels. Two cases were managed medically, and obstetric hysterectomy was needed in the patient with ruptured scar ectopic gestation. Conclusions: Ectopic pregnancy has a rising incidence in today’s world. With the use of better diagnostic modalities, ectopic pregnancies can be detected early and treated appropriately. However, as a silent disease, it presents with subtle signs and symptoms and hence can be easily misdiagnosed. Also, because of its subtle presentations, patients often present late in the course of the disease, wherein management of the condition can be sometimes life - saving. But once diagnosed accurately, it needs prompt treatment. Treatment however is easy and patients respond wonderfully with both medical and surgical management.